Civic Online Reasoning Among Adults: An Empirical Evaluation of a Prescriptive Theory and Its Correlates - Guath, Mona; Nygren, Thomas (Frontiers in Education, 2022)
Today, the skill to read digital news in constructive ways is a pivotal part of informed citizenship. A large part of the research on digital literacy is dedicated to adolescents and not adults. In this study, we address this research gap. We investigated the abilities of 1222 Swedish adults to determine the credibility of false, biased, and credible digital news in relation to their background, education, attitudes, and self-reported skills. Their ability was operationalized as three components in the prescriptive theory of civic online reasoning. Results from a combined survey and performance test showed that the ability to determine the credibility of digital news is associated with higher education, educational orientation in humanities/arts, natural sciences, and technology, the incidence of sourcing at work, and appreciation of credible news. An SEM analysis confirmed that the items used to assess the different skills tapped into the theoretical constructs of civic online reasoning and that civic online reasoning was associated with a majority of the predictors in the analyses of the separate skills. The results provide unique evidence for a prescriptive theory of the skills needed to navigate online.